A Comparative Analysis Of The First-Ever Written Constitution, The Magna Carta And The Charter Of Medina - Owais Anwer; Muhammad Ishaq Alam (الإيضاح, 2023)
The Charter of Madinah is not the world's first written constitution though it has the highest covenant and constitutional characteristics in terms of its content and meaning. The covenant is a distinct constitution emblematic of the Quran and Sunnah. In the light of this constitution, not only Ansaar and Muhajirin but Jews and other minorities lived amicably in Madinah. The Charter of Madinah carries all the fundamental features that an ideal constitution should have. According to the treaty, Madinah was considered the 1st Islamic state which had won acceptance of all the Jewish tribes and clans of other minorities living within the premises of Madinah. In the constitution, the rights of Muslims were explicitly mentioned and it was ensured that rights of all minorities are protected. The treaty was held abiding by all the residents of Medina and all were required to observe the rights of each other. Some historians report that the Magna Carta was the first International treaty or constitution which was reportedly written down in 1215 during the era of King John-I of England. In this article, a comparative analysis has been made between both constitutions focusing the minorities’ rights.